NextBlocks: A collaborative block programming platform - Pereira, Duarte Guerreiro Nunes (2024)
The subject of computer science education has been the object of research and investigation for almost as long as modern computer science itself has existed. Very early on, with Seymour Papert’s work related to the Logo programming language in the 1960s, a view emerged that visual programming environments were ideal for teaching programming to children and novices. As these platforms evolved and became more prevalent, block pro- gramming became the de facto standard for platforms directed at children and beginners. However, modern block programming platforms like Scratch and Code.org excessively restrict educators, not allowing them to create custom exercises in the platform. They also tend to make programming a solitary activity, not allowing for collaboration and cooperation between learners (Scratch is an exception in this point). Additionally, they tend to be in standalone websites, and are not implemented in locations that students already frequent regularly. Having identified these gaps in the field of block programming environments, this dissertation proposes NextBlocks, a new block programming platform implemented as a Moodle plugin. The NextBlocks platform allows the creation of custom exercises by educators, and it has a heavy focus on social perception and collaboration features. The plugin offers features that are uncommon in block programming environ- ments, with the added convenience of being implemented into Moodle, a platform that many students already use regularly. Being open source, it can also serve as a base for any other developers who wish to extend it with new features.